Short rotation coppices, grasses and other herbaceous crops: Productivity and yield energy value versus 26 genotypes. (December 2018) - Stolarski, Mariusz J.; Śnieg, Malwina; Krzyżaniak, Michał; Tworkowski, Józef; Szczukowski, Stefan
Abstract: The diversity of perennial plants requires the proper selection of species and cultivars with high resistance to weather and habitat conditions and high productivity and yield energy value. Therefore, this study analysed the resistance to environmental conditions, survival rate and morphological features, yield and energy value of the yield of 26 genotypes of perennial plants in three annual harvest cycles. The study was carried out in north-eastern Poland and included 15 genotypes of short rotation woody crops, six genotypes of herbaceous plants and five genotypes of grasses. Short rotation woody crops where the most resistant to environmental conditions, whereas grasses and some herbaceous genotypes were the most prone to lodging. The three willow varieties (Ekotur, Żubr and Start) gave the highest average yield (over 15 Mg ha −1  y −1 d.m.) and they yielded over 20 Mg ha −1  y −1 d.m. in 2013, which in terms of energy was equivalent to 350 GJ ha −1  y −1 . Poplars gave more than three times and black locust up to five times lower yield compared to the highest-yielding willows. The highest yield among herbaceous plants was obtained from Helianthus salicifolius, and among grasses – from Miscanthus sacchariflorus (on average 9 Mg ha −1  y −1 d.m.). The yield energy value of these genotypes was approx. twice lower compared to the best willow varieties. It was found that of the 26 genotypes of perennial plants, new willow varieties proved the most valuable in terms of yield and energy in the initial three years under the environmental conditions of north-eastern Poland. Highlights: The study presents the productivity and yield energy value 26 perennial crops. Short rotation woody crops were the most resistant to environmental conditions. The highest yield and yield energy value was given by willow, Ekotur variety. Among herbaceous crops the best results was noted for Helianthus salicifolius. From grasses the best results was obtained for Miscanthus sacchariflorus.